DAMPAK PUTUSAN MAHKAMAH AGUNG DAN MAHKAMAH KONSTITUSI MENGENAI OPEN LEGAL POLICY DI TINJAU DARI HUKUM ADMINISTRASI NEGARA - Lananda, Ardelia; Mulyadi, Dedi; Rahmah, Mila Arastasya; Baidhowi, Nayla Ratu; Simbolon, Cindy Claudia; Januwati, Pusfa (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
In the context of administrative law, the decisions of the Supreme Court (MA) and the Constitutional Court (MK) play a crucial role in shaping open legal policies in Indonesia. Open legal policy refers to policies that provide flexibility for the legislative body to regulate legal content that is not explicitly addressed by the Constitution. This study aims to analyze the impact of the decisions made by the MA and MK on open legal policies from the perspective of administrative law. The method used is a normative legal approach, focusing on the analysis of literature and secondary data. The identification of issues includes the background of the MA and MK decisions regarding open legal policies, the challenges faced by judicial institutions related to these policies, and the efforts of these institutions to make decisions in accordance with their absolute competencies. The findings indicate that the decisions of the MA and MK are essential to ensuring that public policies adhere to the principles of good administrative law, such as legal certainty, transparency, and accountability. These decisions provide boundaries and guidance for policymakers to maintain a balance between legislative freedom and applicable legal principles. This research also highlights the implications of significant rulings, such as the annulment of norms deemed unconstitutional and the affirmation of minimum age limits in regional head elections, offering insights for the development of the administrative law system in Indonesia.